Science Teaching and Learning Activities at Jincheng Junior High School to Support Students’ Scientific Literacy - Kusumaningtyas, Carolina Sari; Pukan, Krispinus Kedati (Journal of Biology Education, 2020)
Scientific literacy is an ability to integrate science knowledge with relevant context and encourage people to behave scientifically. This case study describes the teaching and learning activities at Jincheng Junior High School, Tainan, Taiwan in supporting students’ scientific literacy. This study was a qualitative descriptive study that describes teaching and learning activities in supporting students’ scientific literacy as written in the narrative text. The data was collected by using observation, interview, and documentation. The data was then analyzed through five stages of qualitative data analyses by Nowell et al. (2017). The result shows that there were some key activities conducted at Jincheng Junior High involving laboratory, teaching, assessing, and learning activities. However, there were some limitations of the frequency of conducting laboratory activities and developing students’ inquiry. It can be concluded that teaching and learning activities at Jincheng Junior High School could support students’ scientific literacy.